Estimate of the Stark shift by penetrating ions within the nearest perturber approximation for hydrogenlike spectral lines in plasmas. (16th November 2017) - Sanders, P; Oks, E
Abstract: Red shifts of spectral lines (hereafter, SL) play an important role in astrophysics. For inferring the relativistic red shifts from the observed red shifts it is required to allow for the Stark shift of SL. In laboratory plasmas, measurements of the Stark shift can supplement measurements of the Stark width and thus enhance plasma diagnostics—specifically the determination of the electron density. In the present paper we describe a new source of the Stark shift of hydrogenlike SL. It originates from configurations where the nearest perturbing ion is within the radiating atom/ion ('penetrating configurations'). As an example, we compare the results with the experimental shift of the Balmer-alpha SL of He II 1640 A measured in a laboratory plasma by Pittman and Fleurier (1986 Phys. Rev. A33 1291). We show that the allowance for this new additional red shift leads to a good agreement with the measured shift for the entire range of the electron density employed in that experiment, while without this new shift the previously known shifts underestimated the measured shift by factors between two and five.